Plerion model of the X-ray plateau in short gamma-ray bursts. Issue 4 (13th June 2019) - Strang, L C; Melatos, A
Abstract: Many short gamma-ray bursts (sGRBs) exhibit a prolonged plateau in the X-ray light curve following the main burst. It is shown that an X-ray plateau at the observed luminosity emerges naturally from a plerion-like model of the sGRB remnant, in which the magnetized, relativistic wind of a millisecond magnetar injects shock-accelerated electrons into a cavity confined by the sGRB blast wave. A geometry-dependent fraction of the plerionic radiation is also intercepted and reprocessed by the optically thick merger ejecta. The relative contributions of the plerion and ejecta to the composite X-ray light curve are estimated approximately with the aid of established ejecta models. The plerionic component of the electron energy spectrum is evolved under the action of time-dependent, power-law injection and adiabatic and synchrotron cooling in order to calculate the X-ray light curve analytically. The model yields an anticorrelation between the luminosity and duration of the plateau as well as a sudden cut-off in the X-ray flux, if the decelerating magnetar collapses to form a black hole. Both features are broadly consistent with the data and can be related to the surface magnetic field of the magnetar and its angular velocity at birth. The analogy with core-collapse supernova remnants is discussed briefly.